Typing Discrepancy Between Phenotypic and Molecular Characterization Revealing an Emerging Biovar 9 Variant of Smooth Phage-Resistant B. abortus Strain 8416 in China - Kang, Yao-Xia; Li, Xu-Ming; Piao, Dong-Ri; Tian, Guo-Zhong; Jiang, Hai; Jia, En-Hou; Lin, Liang; Cui, Bu-Yun; Chang, Yung-Fu; Guo, Xiao-Kui; Zhu, Yong-Zhang (Frontiers in Microbiology, 2015)
A newly isolated smooth colony morphology phage-resistant (SPR) strain 8416 isolated from a 45-year-old cattle farm cleaner with clinical features of brucellosis in China was reported. The most unusual phenotype was its resistance to two Brucella phages Tbilisi and Weybridge, but sensitive to Berkeley 2, a pattern similar to that of B. melitensis biovar 1. VITEK 2 biochemical identification system found that both strain 8416 and B. melitensis strains shared positive ILATk, but negative in other B. abortus strains. However, routine biochemical and phenotypic characteristics of strain 8416 were most similar to that of B. abortus biovar 9 except CO2 requirement. In addition, multiple PCR molecular typing assays including AMOS-PCR, B. abortus special PCR (B-ab PCR) and a novel sub-biovar typing PCR, indicated that strain 8416 may belong to either biovar 3b or 9 of B. abortus. Surprisingly, further MLVA typing results showed that strain 8416 was most closely related to B. abortus biovar 3 in the Brucella MLVA database, primarily differing in 4 out of 16 screened loci. Therefore, due to the unusual discrepancy between phenotypic (biochemical reactions and particular phage lysis profile) and molecular typing characteristics, strain 8416 couldn’t be exactly classified to any of the existing B. abortus biovars and might be a new variant of B. abortus biovar 9. The present study also indicates that the present phage typing scheme for Brucella spp. is subject to variation and the routine Brucella biovar typing needs further studies.